2015
DOI: 10.3389/fmicb.2015.00573
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the unexplored fungal communities in deep groundwater of crystalline bedrock fracture zones in Olkiluoto, Finland

Abstract: The diversity and functional role of fungi, one of the ecologically most important groups of eukaryotic microorganisms, remains largely unknown in deep biosphere environments. In this study we investigated fungal communities in packer-isolated bedrock fractures in Olkiluoto, Finland at depths ranging from 296 to 798 m below surface level. DNA- and cDNA-based high-throughput amplicon sequencing analysis of the fungal internal transcribed spacer (ITS) gene markers was used to examine the total fungal diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 53 publications
5
68
0
Order By: Relevance
“…Fungi from the order Pezizomycotina (including the class Dothimdeomycetes) had higher relative abundance in aquifers than wells. This taxon is known to occur within aquifers74, potentially having a significant role in nutrient cycling and biofilm production75.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi from the order Pezizomycotina (including the class Dothimdeomycetes) had higher relative abundance in aquifers than wells. This taxon is known to occur within aquifers74, potentially having a significant role in nutrient cycling and biofilm production75.…”
Section: Discussionmentioning
confidence: 99%
“…Water in predominantly rocky areas, with low solubility, have less diverse ion composition, and are more likely present on the surface or as a groundwater close to the surface [47]. On the other hand, geological structures, such as limestone composed from calcium carbonate, have a significant effect on the formation of specific areas, known as karst systems [48].…”
Section: Fungi and Water—background Informationmentioning
confidence: 99%
“…Groundwater is known to harbour a wide range of specialist taxa which are difficult to assess using conventional survey methods due to the inaccessibility of these habitats (Danielopol et al, 2000). Groundwater microorganism metabarcoding studies have shown high fungal (Sohlberg et al, 2015) and bacterial (Kao et al, 2016) (Valiere & Taberlet, 2000). Environmental DNA metabarcoding of water from glacial run-off will also likely be a valuable tool to survey animal and plant richness living in glacial and subglacial habitats, which are undergoing dramatic change because of climate warming (Giersch, Hotaling, Kovach, Jones, & Muhlfeld, 2017).…”
Section: Species Relative Abundance: Edna Metabarcoding Compared Wimentioning
confidence: 99%